Wolbachia, Cardinium and climate: an analysis of global data. (21st August 2019) - Charlesworth, J.; Weinert, L. A.; Araujo, E. V.; Welch, J. J.
Abstract : Bacterial endosymbionts are very common in terrestrial arthropods, but infection levels vary widely among populations. Experiments and within-species comparisons suggest that environmental temperature might be important in explaining this variation. To investigate the importance of temperature, at broad geographical and taxonomic scales, we extended a global database of terrestrial arthropods screened for Wolbachia and Cardinium . Our final dataset contained data from more than 117 000 arthropods (over 2500 species) screened for Wolbachia and more than 18 000 arthropods (over 800 species) screened for Cardinium, including samples from 137 different countries, with mean temperatures varying from −6.5 to 29.2°C. In insects and relatives, Cardinium infection showed a clear and consistent tendency to increase with temperature. For Wolbachia, a tendency to increase with temperature in temperate climates is counteracted by reduced prevalence in the tropics, resulting in a weak negative trend overall. We discuss the implications of these results for natural and introduced symbionts in regions affected by climate change.